Examination of athletes' anxiety about catching coronavirus (Revista de Investigaciones Universidad del Quindío, 2022)
The coronavirus epidemic affected not only China but also several countries in the world. The survey aims to analyze the concerns of athletes about contracting Covid-19. The sample of the study consists of 293 volunteer participants living in Iğdır province and doing sports in different branches. This research is in the scanning model and has a descriptive nature. The data were collected through the 'personal information form' to define the demographic data of the participants, and the "Anxiety Scale of Athletes catching New Type Coronavirus (Covid-19)". Given the results, the athletes are worried about catching the coronavirus, but lack of statistically significant results in the relationship of the variables used in the research with the anxiety of contracting the coronavirus, the geographical region where the athletes live, the supervision of the measures taken within the scope of the coronavirus can be considered as the psychological consequences of the social environment.
Keywords: Athlete; Coronavirus; Anxiety; Athletes; Psychological Consequences